Effect of Thickness on Structural and Optical properties of ZnS:Mn films Prepared by RF magnetron Sputtering Method - Azhar Mohammed Abed; Abdulhussain K. Elttayef; Khalid Hamdi Razeg (Tikrit Journal of Pure Science, 2019)
In this study, ZnS: Mn thin films prepared by RF magnetron sputtering technique, were mixed 20 g of ZnS with Mn (2%), and deposited on glass substrate at temperature of 100oC with different thickness (404, 775, and 900) nm. The prepared films were investigated by X-ray diffraction (XRD), atomic force microscopic(AFM), scanning electronic microscopic (SEM), and UV-VIS spectrophotometer. XRD results shows that the films have single crystallization nature with cubic crystal structure (Zinc blende) and strong peaks at (111) as highly preferential orientation. SEM and  AFM analysis indicates that the diameter of particles were found to be nanometer, it ranged up to 29.55nm, 89.42nm at thickness (900nm) respectively. The results of UV-Vis spectrophotometry show that the transparency of films with different thickness was found to be around 53.43-86.63% in visible range. The band gap energies are calculated to be between 3.20-3.70 eV.